Performance and Economic Evaluation of Asphalt-Based High Friction Surface Treatment (HFST) Applications - Alireza Roshan; Magdy Abdelrahman (Applied Sciences)
High Friction Surface Treatments (HFSTs) are recognized for enhancing friction between tires and road surfaces, with reduced road accidents being a key benefit. Epoxy-based HFSTs, though widely used, come with challenges like compatibility issues with existing pavements, higher installation and removal costs, and reduced durability tied to substrate quality. Recently, state agencies have increasingly focused on developing asphalt-based alternative binders for HFST applications as highlighted in the National Cooperative Highway Research Program (NCHRP) RFP #NCHRP 10-145. This study introduces asphalt-based HFSTs as an alternative to traditional epoxy-based treatments. Various aggregate types were examined for friction performance and the effect of polishing cycles on asphalt-based HFST. Tests such as the British Pendulum Test (BPT), Dynamic Friction Tester (DFT), and Circular Track Meter (CTM) were conducted to assess the Coefficient of Friction (COF) and Mean Profile Depth (MPD) before and after polishing cycles. Additionally, a Life Cycle Cost Analysis (LCCA) was performed to determine the economic advantages of asphalt-based HFSTs over epoxy treatments. The goal was to develop a method to convert diverse project and material data into comparable outputs like net present value (NPV), enabling comparisons between alternatives. Results from the LCCA demonstrated that the use of specific asphalt-based binders combined with optimized aggregate gradation not only achieves performance levels comparable to traditional HFST options but also improves cost efficiency.